Anti-TNF alpha/azathioprine therapy modulates the Natural killer cell compartment in pediatric inflammatory bowel disease - Knieling, Ferdinand; Schnell, Alexander; Allabauer, I.; Schwarz, B.; Rechenauer, Tobias; Kaspar, S.; Siebenlist, G.; Rueckel, A.; Hartmann, Arndt; Wahlbuhl-Becker, Mandy; Hoerning, A. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Attenuation of Mammary Gland Dysplasia and Feeding Difficulties in Tabby Mice by Fetal Therapy - Wahlbuhl, Mandy; Schuepbach-Mallepell, Sonia; Kowalczyk-Quintas, Christine; Dick, Angela; Fahlbusch, Fabian B.; Schneider, Pascal; Schneider, Holm (Journal of Mammary Gland Biology and Neoplasia, 2018)
Hypohidrotic ectodermal dysplasias (HED) are hereditary differentiation disorders of multiple ectodermal structures including the mammary gland. The X-linked form of HED (XLHED) is caused by a lack of the secreted signaling molecule ectodysplasin A1 (EDA1) which is encoded by the gene EDA and belongs to the tumor necrosis factor (TNF) superfamily. Although male patients (hemizygous) are usually more severely affected by XLHED, heterozygous female carriers of an EDA mutation may also suffer from a variety of symptoms, in particular from abnormal development of their breasts. In Tabby mice, a well-studied animal model of XLHED, EDA1 is absent. We investigated the effects of prenatal administration of Fc-EDA, a recombinant EDA1 replacement protein, on mammary gland development in female Tabby mice. Intra-amniotic delivery of Fc-EDA to fetal animals resulted later in improved breastfeeding and thus promoted the growth of their offspring. In detail, such treatment led to a normalization of the nipple shape (protrusion, tapering) that facilitated sucking. Mammary glands of treated female Tabby mice also showed internal changes, including enhanced branching morphogenesis and ductal elongation. Our findings indicate that EDA receptor stimulation during development has a stable impact on later stages of mammary gland differentiation, including lactation, but also show that intra-amniotic administration of an EDA1 replacement protein to fetal Tabby mice partially corrects the mammary gland phenotype in female adult animals.
EVALuna2:35485

Correction of Vertebral Bone Development in Ectodysplasin A1-Deficient Mice by Prenatal Treatment With a Replacement Protein - Kossel, Clara-Sophie; Wahlbuhl-Becker, Mandy; Schuepbach-Mallepell, Sonia; Park, Jung; Kowalczyk-Quintas, Christine; Seeling, Michaela; von der Mark, Klaus; Schneider, Pascal; Schneider, Holm (Frontiers in Genetics, 2021)
X-linked hypohidrotic ectodermal dysplasia with the cardinal symptoms hypodontia, hypotrichosis and hypohidrosis is caused by a genetic deficiency of ectodysplasin A1 (EDA1). Prenatal EDA1 replacement can rescue the development of skin appendages and teeth. Tabby mice, a natural animal model of EDA1 deficiency, additionally feature a striking kink of the tail, the cause of which has remained unclear. We studied the origin of this phenomenon and its response to prenatal therapy. Alterations in the distal spine could be noticed soon after birth, and kinks were present in all Tabby mice by the age of 4 months. Although their vertebral bones frequently had a disorganized epiphyseal zone possibly predisposing to fractures, cortical bone density was only reduced in vertebrae of older Tabby mice and even increased in their tibiae. Different availability of osteoclasts in the spine, which may affect bone density, was ruled out by osteoclast staining. The absence of hair follicles, a well-known niche of epidermal stem cells, and much lower bromodeoxyuridine uptake in the tail skin of 9-day-old Tabby mice rather suggest the kink being due to a skin proliferation defect that prevents the skin from growing as fast as the skeleton, so that caudal vertebrae may be squeezed and bent by a lack of skin. Early postnatal treatment with EDA1 leading to delayed hair follicle formation attenuated the kink, but did not prevent it. Tabby mice born after prenatal administration of EDA1, however, showed normal tail skin proliferation, no signs of kinking and, interestingly, a normalized vertebral bone density. Thus, our data prove the causal relationship between EDA1 deficiency and kinky tails and indicate that hair follicles are required for murine tail skin to grow fast enough. Disturbed bone development appears to be partially pre-determined in utero and can be counteracted by timely EDA1 replacement, pointing to a role of EDA1 also in osteogenesis.
CRIS-Team Scopus Importer:2021-09-10
Keywords: bone; development; ectodermal dysplasia; ectodysplasin A1; fetal therapy; NF-κB

CXCR4 blockade reduces the severity of murine heart allograft rejection by plasmacytoid dendritic cell-mediated immune regulation - Fu, Jian; Lehmann, Christian; Wang, Xinning; Wahlbuhl, Mandy; Allabauer, Ida; Wilde, Benjamin; Amon, Lukas; Dolff, Sebastian; Cesnjevar, Robert; Kribben, Andreas; Wölfle, Joachim; Rascher, Wolfgang; et al. (Scientific Reports, 2021)
Allograft-specific regulatory T cells (Treg cells) are crucial for long-term graft acceptance after transplantation. Although adoptive Treg cell transfer has been proposed, major challenges include graft-specificity and stability. Thus, there is an unmet need for the direct induction of graft-specific Treg cells. We hypothesized a synergism of the immunotolerogenic effects of rapamycin (mTOR inhibition) and plerixafor (CXCR4 antagonist) for Treg cell induction. Thus, we performed fully-mismatched heart transplantations and found combination treatment to result in prolonged allograft survival. Moreover, fibrosis and myocyte lesions were reduced. Although less CD3+ T cell infiltrated, higher Treg cell numbers were observed. Noteworthy, this was accompanied by a plerixafor-dependent plasmacytoid dendritic cells-(pDCs)-mobilization. Furthermore, in vivo pDC-depletion abrogated the plerixafor-mediated Treg cell number increase and reduced allograft survival. Our pharmacological approach allowed to increase Treg cell numbers due to pDC-mediated immune regulation. Therefore pDCs can be an attractive immunotherapeutic target in addition to plerixafor treatment.
CRIS-Team Scopus Importer:2021-12-24

CXCR4-SDF1 alpha Blockade Reduces the Severity of Murine Heart Allograft Rejection - Fu, J.; Wahlbuhl, Mandy; Wang, X.; Wilde, B.; Jing, L.; Kribben, A.; Hoyer, P.; Lehmann, C. H. K.; Dudziak, Diana; Witzke, O.; Hoerning, A. (2017)
EVALuna2:34369

Distribution and Cytokine Profile of Peripheral B Cell Subsets Is Perturbed in Pediatric IBD and Partially Restored during a Successful IFX Therapy - Schnell, Alexander; Schwarz, Benedikt; Wahlbuhl, Mandy; Allabauer, Ida; Hess, Merlin; Weber, Simone; Werner, Felix; Schmidt, Hannah; Rechenauer, Tobias; Siebenlist, Gregor; Kaspar, Sonja; Ehrsam, Christoph; et al. (Inflammatory Bowel Diseases, 2021)
Background: The role of B cells in inflammatory bowel disease (IBD) is ambiguous, as B cells may have both pathogenic and protective functions in IBD. We studied B cell subsets before and after initiation of an anti-tumor necrosis factor alpha (anti-TNFα) therapy in pediatric IBD. The aim of the study was to examine the behavior of B cells in pediatric IBD patients undergoing an anti-TNFα therapy and, more specifically, to clarify their association with a successful or an unsuccessful infliximab (IFX) treatment. Methods: A total of N = 42 pediatric IBD patients (Crohn disease, n = 30; ulcerative colitis, n = 12) for whom an anti-TNFα therapy with and without a concomitant azathioprine (AZA) medication was administered were recruited. Fourteen healthy age-matched children served as control patients. Blood samples were collected before initiation of the anti-TNFα therapy, before the fourth infusion at the end of the induction phase, and after 6 and 12 months under therapy maintenance. Flow cytometry (CD20, CD27, CD38, CD138) and intracellular staining (interleukin 10 [IL10], TNFα, granzyme B) were performed. Responders to successful IFX therapy were classified exhibiting a fecal calprotectin level of below 100 μg/g or achieving levels of <10% of the baseline value at initiation than at the end of the 12-month follow-up period. Results: Before initiation of anti-TNFα therapy, flow cytometry revealed increased percentages of naïve B cells whereas transitional B cells were reduced compared with those in the healthy control patients. The IL10-producing B cells of both ulcerative colitis and Crohn disease patients were reduced at the initiation of IFX therapy, whereas TNFα-producing transitional CD24hiCD38hi B cells in ulcerative colitis patients were increased compared with those in healthy control patients. After 12 months of therapy, we detected a significant increase of IL10-producing transitional B cells in responding patients. The IFX trough levels in the responding patients showed a significant increase until 6 months after IFX initiation, attaining mean values of 9.9 μg/mL, whereas the IFX dosage was significantly lower than that in the nonresponding patients. The IFX trough levels in AZA-treated patients reached earlier therapeutic levels than in patients without AZA comedication, whereas during the course of the IFX therapy, comedication with AZA had no significant effect on the outcome. Conclusions: Attaining a normalization of IL10 production among CD24hiCD38hi B cells after 12 months of therapy may represent additional information about the reconstitution of a patient's immune system in responding patients. The achievement of an IFX trough level of 10 μg/mL at 6 months of treatment is associated with a successful anti-TNFα therapy. In addition, AZA comedication supports an earlier achievement of therapeutic IFX trough levels.
CRIS-Team Scopus Importer:2021-02-26
Keywords: children; Crohn disease; TNFα inhibitor; transitional B cells; ulcerative colitis

Frequency of B-cell subsets in infliximab-treated paediatric IBD patients - Schnell, Alexander; Schwarz, B.; Wahlbuhl-Becker, Mandy; Allabauer, I.; Rechenauer, Tobias; Siebenlist, G.; Kaspar, S.; Ehrsam, C.; Rueckel, A.; Rascher, Wolfgang; Hoerning, A. (JOURNAL OF CROHNS & COLITIS, 2019)
CRIS-Team WoS Importer:2019-03-20

Hypohidrotic Ectodermal Dysplasia: Breastfeeding Complications Due to Impaired Breast Development - Wahlbuhl-Becker, Mandy; Faschingbauer, Florian; Beckmann, Matthias; Schneider, Holm (Geburtshilfe und Frauenheilkunde, 2017)
Background X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common form of ectodermal dysplasia, is caused by mutations in the gene EDA. While only affected men develop the full-blown clinical picture, females who are heterozygous for an EDA mutation often also show symptoms such as hypodontia, hypotrichosis and hypohidrosis. These women may also suffer from malformations of the mammary gland which represent not just a cosmetic problem but can limit their breastfeeding capability. This paper summarizes the findings of the first systematic study on the impact of hypohidrotic ectodermal dysplasia on breastfeeding. Patients Thirty-eight adult female members of the German-Swiss-Austrian ectodermal dysplasia patient support group participated in a structured interview; most of them also agreed to a photodocumentation of their mammary region. Thirty-one women carried mutations in EDA (Group A) and seven were affected by other forms of hypohidrotic ectodermal dysplasia (Group B). Results 39 % of the women of Group A reported that their breasts were of different size or entirely absent on one side. In Group B, 86 % of the women reported differently sized or even absent breasts; two of these women lacked both breasts entirely. Most women described their nipples as exceptionally flat. 10 % of the women of Group A had more than two nipples. The high percentage of deviations from the norm was confirmed in the photodocumentation. Both groups had few or no sebaceous glands of Montgomery in the areolar region. Around 80 % of interviewed women had children and had attempted to breastfeed their first child. 67 % of the mothers in Group A had had difficulty in breastfeeding their infants and generally attributed this difficulty to their flat nipples. All of the mothers in Group B reported difficulties in breastfeeding; 60 % had not been able to breastfeed their first child. Conclusion Mothers with hypohidrotic ectodermal dysplasia very often have difficulty in breastfeeding because of their impaired breast development. This causal relationship needs to be taken into account in lactation counseling.
EVALuna2:34219

Prenatal Correction of X-Linked Hypohidrotic Ectodermal Dysplasia - Schneider, Holm; Faschingbauer, Florian; Schuepbach-Mallepell, Sonia; Koerber, Iris; Wohlfart, Sigrun; Dick, Angela; Wahlbuhl, Mandy; Kowalczyk-Quintas, Christine; Vigolo, Michele; Kirby, Neil; Tannert, Corinna; Rompel, Oliver; et al. (New England Journal of Medicine, 2018)
Genetic deficiency of ectodysplasin A (EDA) causes X-linked hypohidrotic ectodermal dysplasia (XLHED), in which the development of sweat glands is irreversibly impaired, an condition that can lead to life-threatening hyperthermia. We observed normal development of mouse fetuses with Eda mutations after they had been exposed in utero to a recombinant protein that includes the receptor-binding domain of EDA. We administered this protein intraamniotically to two affected human twins at gestational weeks 26 and 31 and to a single affected human fetus at gestational week 26; the infants, born in week 33 (twins) and week 39 (singleton), were able to sweat normally, and XLHED-related illness had not developed by 14 to 22 months of age. (Funded by Edimer Pharmaceuticals and others.).
EVALuna2:35486

Surprising prenatal toxicity of epidermal lipoxygenase-3 - Vierling, F.; Dick, Angela; Wahlbuhl, Mandy; Krieg, P.; Henke, Christine; Ruebner, M.; Schneider, Holm (Placenta, 2014)
Metabolites of the epidermal lipoxygenase-3 (eLOX-3) are involved in various metabolic pathways. Most unexpectedly, intra-amniotic delivery of eLOX-3 to mice at gestational day 14.5, both via an adenoviral vector and as recombinant protein, resulted in fetal growth restriction and intrauterine death. Periodic acid-Schiff staining and RT-PCR analysis of placentae from fetuses exposed to eLOX-3 indicated a lack of glycogen trophoblasts in the junctional zone. Placenta-specific gene expression was altered. Thus, the observed prenatal toxicity of eLOX-3 could be due to a strong effect on placental development.
EVALuna2:17431